Are There Differences in Life-Satisfaction, Optimism, Pessimism and Perceived Stress between Therapeutic and Mastery Exercisers? A Preliminary Investigation (Baltic Journal of Sport and Health Sciences, 2019)
Background. Most incentives for exercise can be grouped into health-related ‘therapeutic’ and challenge or enjoyment-related ‘mastery’ categories. If these incentives are not independent of personal needs and expectations, their associated psychological profiles may vary.Methods. Based on the broaden-and-build theory, we examined the hypothesis that mastery exercise is associated with more favourable psychological profile, as reflected in greater life-satisfaction, optimism, pessimism, and perceived stress, than therapeutic exercise or no-exercise (the control group).Results. The results indicated that people who exercised for a mastery purpose (n = 57) reported greater optimism, lower pessimism and lower perceived stress than non-exercisers (n = 57) but they only scored higher in optimism in contrast to the therapeutic exercisers (n = 129) who did not differ from the controls in any of the measures. A composite score of a psychological profile, obtained by subtracting the sum of negative ratings from the sum of positive ratings, revealed that mastery exercisers exhibited higher scores than non-exercisers who did not differ from therapeutic exercisers.Conclusion. These preliminary findings suggest that two very general motives for exercise might be associated with different psychological profiles, which deserves future research attention in the better understanding of the psychological effects of exercise. Keywords: life-satisfaction, optimism, non-exerciser, perceived stress, pessimism.